Effect of Flaxseed Supplementation in the Maternal Diet During Early Lactation on the Oxidative Status of Sows and Growth of Piglets - Kaur, Sukhjinder; Singh, Ashwani Kumar; Honparkhe, Mrigank; Singh, Prahlad; Singh, Udeybir (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on 21 crossbred Large White Yorkshire sows to assess the effect of flaxseed supple mentation on oxidative stress in sows and growth of piglets. All sows were equally allocated into three groups. Group 1 served as the control and followed their normal feeding schedule. Group 2 and group 3, in addition to their normal feed ing schedule, were supplemented with flaxseed at a rate of 0.5% and 1.0% of the dry matter, respectively. Blood samples were collected 15 days prior to farrowing, on the day of farrowing (day 0), at weekly intervals until day 28 of lactation and at monthly intervals during gestation to assess the oxidative status in each sow. Body weight and weight gain in each piglet was measured during lactation period. The assessment of oxidative stress in blood was done through estimations of malondialdehyde (MDA), end product of lipid peroxidation. No changes (P>0.05) in MDA concentrations were mani fested at any of the days measured during lactation and gestation in sows of all the groups. Similarly, there was no effect of flaxseed treatment on superoxide dismutase (SOD) levels in all sows at any of the days measured during lactation period (P>0.05) as well as during gestation period (days 30-90). In the current farrowing, the piglets exhibited a steady increase (P<0.05) in bodyweight as well as weight gain in all groups from day 0 until day 28 of lactation. No effect (P>0.05) of flax seed fed to sows on litter weight and weight gain was noticed until day 21 of lactation, However, the effect of treatment was evinced on day 28 of lactation compared to control group. In conclusion, flaxseed supplementation had no impact on MDA and SOD concentrations in sows; nevertheless a treatment effect was noticed on body weight and weight gain in piglets.